The Difference of Composite Resin Compressive Strength with Sidikalang Coffee Soaking - Mangatas H.P. Hutagalung; Benarivo T Ginting; Sucy Erawati; Sri Yasa Hasibuan; Cindy Amalia P (Archives of The Medicine and Case Reports, 2021)
Composite resin is a caries filling material. Generally, dentists choose this type ofresin as a restoration material because this material has a high compressivestrength. There are several factors that influence the compressive strength ofcomposite resins, including beverages consumed such as coffee. This study aims todetermine the difference in the compressive strength of the composite resin withSidikalang coffee immersion in 9 hours, 27 hours and 54 hours immersion time.This type of research is experimental laboratories with posttest only control groupdesign. The research sample was composite resin measuring 8 mm in diameter and4 mm in height. The sample size is determined by the Federer formula and a totalsample of 24 was obtained for the four treatment groups. Measurement ofcompressive strength using a three-point bending tool on a universal testingmachine. Data were analyzed by using the oneway Anova test. Based on the resultsof the study, the average compressive strength of composite resin in the groupwithout immersion, 9 hours, 27 hours and 54 hours of immersion was 20.69 ± 0.84,18.94 ± 0.41, 14.36 ± 0.66 and 6.70 ± 0.48. From the results of the study it can beconcluded that the ads are a significant difference in the average compressivestrength of composite resin after immersion in Sidikalang coffee for 9 hours, 27hours and 54 hours.